2015
DOI: 10.1007/s00425-014-2236-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a plant albumin from Cicer arietinum (chickpea) possessing hemopexin fold and hemagglutination activity

Abstract: Crystal structure of a reported PA2 albumin from Cicer arietinum shows that it belongs to hemopexin fold family, has four beta-propeller motifs and possesses hemagglutination activity, making it different from known legume lectins. A plant albumin (PA2) from Cicer arietinum, presumably a lectin (CAL) owing to its hemagglutination activity which is inhibited by complex sugars as well as glycoproteins such as fetuin, desialylated fetuin and fibrinogen. The three-dimensional structure of this homodimeric protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The CW-25 protein isolated from Cicer arietinum L. is shown to have mild hemagglutination activity [10,13]. It has also been shown to have antifungal activity [10].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The CW-25 protein isolated from Cicer arietinum L. is shown to have mild hemagglutination activity [10,13]. It has also been shown to have antifungal activity [10].…”
Section: Discussionmentioning
confidence: 98%
“…However, CAL protein contained two other metal ions, calcium and sodium in a channel-like structure. This protein was reported with a mild hemagglutination activity [13]. The role of this protein vis-à-vis metal ion was unclear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An unexpected four-bladed β-propeller structure was found to occur in a PA 2 albumin from chickpea ( Cicer arietinum ), which displays a well documented hemagglutinating activity most probably related to a lectin with an unusual hemopexin fold [171].…”
Section: Structural Organization Of the Plant Algal And Fungal Mamentioning
confidence: 99%
“…The previous reports of chickpea lectin on various aspect take account of characterization of a clone encoding vegetative lectin from C. arietinum epicotyls (Esteban et al 2002), production of stable transgene chickpea through expression of insecticidal lectin (Chakraborti et al 2009) and root lectins (Agrawal et al 2011). In addition, in silico studies on recombinant chickpea lectin (Wakankar et al 2013), three dimensional structure determination (Sharma et al 2015), and α-amylase inhibitory activity against potato beetle larvae (Wang et al 2017) are also published in literature domain. Our previous studies reported crystallization and preliminary X-ray characterisation of a lectin from chickpea (Katre et al 2005).…”
Section: Introductionmentioning
confidence: 99%